Examining Thyroid Testing Practices and Relevant Costs for Children Experiencing Chronic Constipation - Deniz Yaprak; Melike Arslan; Necati Balamtekin; Murat Gülşen (Güncel Pediatri)
Introduction: The study aims to evaluate trends in thyroid testing and direct medical costs incurred by clinical visits and thyroid function tests in children with constipation. Materials and Methods: Hospital records identified children with chronic constipation with an ICD code of K59.0. The number of follow-up visits, thyroid hormone test results, and tests performed for each patient were extracted. Patients treated before were compared to those treated after the launch of the Nationwide Neonatal Screening Program (NNSP) for congenital hypothyroidism. Medical costs were calculated based on the current exchange rate for the US dollar. Results: 2126 follow-up visits and 1363 thyroid function tests were performed for 1128 constipated children. The total number of patients referred before and after the launch of the NNSP was 182 (16.1%) and 946 (83.9%), respectively. Of whom, 937 (%83.1) underwent thyroid testing, and the reported prevalence of hypothyroidism was %6.4 (60). Patients admitted before the launch of NNSP had a significantly higher mean age (12.57±0.89 years) compared to those admitted after (5.14±1.44) (p<0.001). Repeat thyroid testing for patients without hypothyroidism before was higher than after the launch of NNSP; 45.2% (59) vs. 31.9% (210), respectively (p=0.001). The mean cost incurred to diagnose a new patient with hypothyroidism was higher than a standard patient: 70 USD vs 53 USD respectively. The billed per-patient cost for children without hypothyroidism was higher before than after the launch of the NNSP: 46 USD vs 38 USD, respectively. Conclusion: The NNSP implementation for congenital hypothyroidism has reduced the age of patients referred for chronic constipation and modified thyroid testing protocols for clinicians. Unnecessary thyroid testing in children with chronic constipation and dysregulation of operation in the general health insurance coverage system increases medical costs, and the NNSP for congenital hypothyroidism is connected with decreasing medical costs.